“STCKING PICTURES” AS A MEANS OF TEACHING VOCABULARY ON ANIMALS TO THE SECOND GRADERS (RETAIN, 2014)
“STCKING PICTURES” AS A MEANS OF TEACHING VOCABULARY ON ANIMALS TO THE SECOND GRADERS Eka Wulan Sari English Department, Language and Arts Faculty, State University of Surabaya Ekabulan50@yahoo.com Theresia Kumalarini English Department, Language and Arts Faculty, State University of Surabaya Kumalarini_52@yahoo.co.id Abstract Teaching vocabulary should be made enjoyable for the students to make them easy to remember the new words they have just learned. So the teachers have to use the right media to teach young learners especially second graders. The problem is, the teacher still uses the old method, i.e. showing the pictures only. Based on the problem, the researcher used sticking pictures for this study. This study concerns with the implementation and the students’ responses to sticking pictures for teaching vocabulary on animals to the second graders. To get the data needed, the researcher uses observation checklist, interview, and questionnaire as the instruments. The meeting was conducted twice. The data collected were analysed qualitatively through the process of describing, sorting and analysing. The result showed that the sticking pictures was easily implemented. The responses of the students showed that they were very excited to learn vocabulary by using sticking pictures. It means that the media could be used in teaching new vocabulary to the second graders. Keywords: Sticking pictures, Vocabulary, Second graders. Abstrak Mengajar bahasa inggris untuk murid-murid seharusnya menyenangkan agar membuat mereka mudah mengingat kosakata baru yang telah mereka pelajari. Sehingga para pengajar harus menggunakan media yang tepat untuk mengajar anak-anak terutama murid kelas 2 SD. Permasalahannya adalah guru masih menggunakan metode lama yaitu hanya menunjukkan gambar. Berdasarkan permasalahannya, peneliti menggunakan media menempel gambar untuk penelitian ini. Penelitian ini mengenai implementasi dan respon siswa siswi kelas 2 SD dalam penerapan media menempel gambar untuk mengajar kosakata pada bab hewan. Untuk mendapatkan data yang dibutuhkan, peneliti melakukan observasi, wawancara, dan memberikan angket berupa pertanyaan. Pertemuannya dilakukan selama dua kali. Data yang diambil adalah dianalisis secara kualitatif melalui proses menggambarkan, memilah, dan menganalisis. Hasilnya terlihat bahwa media menempel gambar mudah diterapkan. Respon siswa siswi menunjukkan bahwa mereka sangat antusias belajar kosakata menggunakan media menempel gambar. Itu berarti medianya bisa digunakan dalam mengajar kosakata baru untuk siswa siswi kelas 2 SD. Kata kunci: Media menempel gambar, Kosakata, SD kelas 2 Introduction Vocabulary is the important knowledge of English. Chengqian (2009) states that Vocabulary is the basic factor necessary for mastering a language. Because of that, the young learners should learn the vocabulary to develop their knowledge. Teaching vocabulary to the second graders is recommended because what the children learn is what the children do. They will be easy to catch something and put it in their brain. Teaching English vocabulary to young learners is not easy because young learners usually get bored easily. Besides that, second graders are so sensitive. As a teacher, they must have a special strategy to control the students in order to make them respect with the materials that the teacher gives. They usually do the activity that makes them enjoy, such as playing, colouring, cutting, sticking, etc. In addition Harmer (2012) states that children learn best through playing and other enjoyable activities. When introducing English vocabulary to children, the teacher cannot use the old method that is only showing the pictures, memorizing the words in isolation, listing the words and saying them again and again. This technique cannot be recommended anymore to teach vocabulary to the second graders, because the students will not know exactly when and how to use the words taught. The teacher should be able to determine the strategy which suits the characteristics of young learners, among others are those related to pictures. Based on the explanation above, one of the ways to make second graders interested in learning English is that the technique should make the students do an activity relating to using pictures. Such a strategy can help students know when and how to use the words. The pictures can support and help the students remember the words, to know kind and use of the words. Moreover the use of pictures can make the students pay more attention to the material. As Joklova (2009) stated that learners always pay attention and curious about what they are going to do with the pictures shown. Finally, it can be proposed if sticking pictures can be used as a teaching media to teach English vocabulary on animals to the second graders. This is meant to help students focus on the lesson while they learn English vocabulary. Sticking pictures is a media of teaching by using pictures. This activity is similar to the young learners level to do sticking pictures. In this study, sticking pictures is an activity in which children put the coloured picture in a peace of paper that has the same picture and there is spelling the name of the words above the picture. The pictures are focused on animals, then the teacher can expect words like naming animals, also where they live, what they produce, etc. In sticking pictures, the teacher will give the instruction to the students so that they understand and follow the teacher’s saying to help their pronunciations too. Learning English vocabulary by sticking pictures can make them feel that they are not learning but doing an activity they like. It is enjoyable to study and makes the lesson more interesting. So, the researcher uses Sticking Pictures as a means of teaching English vocabulary on animals to the second graders. She tries to describe how sticking pictures is done in a classroom and how do the students respond to the teaching vocabulary on animals through sticking pictures. Methods This study uses descriptive qualitative research to observe and describes the situation that happens in teaching process by using sticking pictures. According to Fraenkel and Wallen (1996), descriptive qualitative is a kind of research in which the data are in the forms of words or pictures (not numerical or quantifiable indicators). This research is focused on every detail situation is like situation of teaching – learning process, problems, students’ interest, etc. They are explored, analysed, and described. It is expected that the researcher will come out with complete information on the processes. In this research, the researcher did not take part in the class as a teacher. She was only an observer. In this study the researcher observed students’ activities and the teacher’s activity in applying the media. The proposed media was attempted for the second graders. The researcher also explained the rules and mechanism of activities that the students did happen in the classroom. The subject of the study was the teacher and the second graders of SDN Gadel 2/557 Surabaya. There were 33 students in class, 14 of whom were female and others were male. The researcher chose them as a subject to be observed because she believed that in this level the students begin to read and write in a simple way. The data of the study were taken from the observation of teaching – learning processes, the teacher’s opinion during the interview and questionnaire for the students. The data were needed to find out whether or not sticking picture technique could be used to introduce new English vocabulary. To collect the data needed for this study, the researcher used observation checklist, interview, and questionnaire. Observation checklist was used to guide the researcher in observing the teaching and learning process. It was conducted twice. The interview was used to interview the teacher in order to get the information about the media, the material, the teaching learning process and the problems. It was conducted at the last meeting in an informal situation. The last was questionnaire which was used to know the students’ responses on how the media is applied in their English study. It was conducted at the last meeting in an informal situation too. After the data were complete, the researcher analysed them descriptively. The data were classified based on the research questions. The researcher described the observation concerning what was going on in the classroom while the teacher implemented “sticking pictures” in teaching vocabulary. Having analysed the data, the conclusion of the result was written descriptively. RESULT How is sticking pictures applied to teach vocabulary on animals to the second graders and how do the students respond to the teaching of vocabulary through sticking pictures. The first observation was done on February 21st 2014. The topic was “animals”. Before sticking pictures was applied, the teacher prepared the media in terms of pictures of various animals and asked them about animals, such as their pets. He explained and showed the pictures about wild and tame animals. While the teacher pointed out and named the pictures, the students followed him to say the names of the animals. After explaining what wild and tame animals were, he asked the students and pointed out some pictures and corrected the students’ pronunciation. The teacher drilled them for several times until they could pronounce all the words well. Here is one of dialogues which the teacher pointed out: Figure 4.1 dialogues between teacher and students The teacher did similar dialogues for all the pictures that he pointed out. The teacher made sure that all students had memorised and understood the vocabularies. Then the teacher gave the handout and stickers to the students. Each student got a piece of paper and a bundle of stickers. There are ten pictures of animals on sticker that should be stuck on the same picture and there was spelling of animals’ name in each picture on a piece of paper that the teacher had given to them. After that the teacher gave the instructions clearly. In these activities, the students focused on matching the animals and worked by themselves. There were some students who still did not understand how to name the animals. Then the teacher guided them to name the animals by giving an example. To apply the media, the teacher used the following kinds of pictures: Figure 4.2 Pictures of Animals introduced at the first meeting After the students finished their work, the teacher asked to submit their work. Then he shared the students’ work to the students who had different names to check their answer together. In this activity, the teacher discussed the answer from picture one to the end and pronounced the animals one by one. It made the students easier to remember the vocabularies. Here are some dialogues in the discussion: Figure 4.3 dialogues between teacher and students. The teacher had similar dialogues until the last pictures. After completing the work, the teacher asked the students about what they had learned and asked their feeling about their study. They were very happy to have studied like that. It made them enthusiastic in learning new vocabularies on animals. The second observation was held on February 28th 2014. He explained to the students about what was going on that day. The teacher asked the students to open their book. He explained more information about the animals such as what the animals’ produce, where the animals live and how the animals were classified. Here is one of dialogues in the teaching learning process: Figure 4.4 dialogues between teacher and students. The teacher did like the dialogue above until the end of the pictures shown. After explaining, the teacher did not give the handout like the one at the previous meeting. He only gave them a game. The game included the media, i.e. sticking pictures. He divided the class into four groups. Each group consisted of eight students. Then he asked each group to choose the leader. After that he asked the leader of the group to come forward to get an envelope for each group and pay attention to the instructions of how to play the game. The instruction was that the teacher gave three questions, if they answered the questions correctly, they could stick the picture up on the board including the name of the animal. Here are the pictures of animals which the teacher used to apply the media: Figure 4.5 Pictures of Animals introduced at the second meeting In this activity, some groups were sticking the pictures in a wrong place, because they did not see the text. So, the teacher had an initiative to name the pictures with the number of the groups, in order to know which group had completed the game. When applying this media, the students were very enthusiastic. All students wanted to stick up the pictures and the name of the animals. Suddenly, some students came forward to help their member to stick the pictures and named up. They did not listen their teacher’s questions, because they had already known the pictures and the names. So it made the condition chaotic and uncontrolled. There were only two groups which were successful completing the game without listening to the teacher’s questions. After that, the teacher discussed the answers together. It was like the one in the previous meeting. After applying the media, the teacher let the students pronounce the name of the animals together by pointing the pictures. Here is the dialogue being discussed:Figure 4.6 dialogues between teacher and students. At the end of the teaching learning process, the teacher asked their feeling about their study. They felt happy to have studied vocabulary like this. They wanted to study vocabulary like this again. They stated that it was very fun. It means that the students were very interested in the media that the teacher used. State Council of Educational Research and Training Varun Marg, Defence Colony (2011) stated that vocabulary is best learned when the meaning of the word(s) is illustrated by a picture, an action or a real object. These media was made in order to make the students easier in remembering the new vocabularies. So, using pictures is a recommended media in teaching vocabulary on animals and the topic should be appropriate with the students’ curriculum of the second graders. Based on the teacher’s opinion, he stated that in the teaching learning process, the media was easy to apply and made the students more active in learning vocabulary. The media could make the students easy to remember the new vocabulary. As a result, he found that it was not difficult to drill them in studying new vocabulary using pictures, because the students were interested enough with the pictures. The teacher sometimes found difficulties such as that in the second meeting. When applying games, the students were uncontrolled. So he changed the instruction by giving numbers to each group based on the number of the group. After that, the condition was back to normal and the students were very excited to study new vocabulary by sticking pictures in a game. To get the responses of the students, the researcher conducted a questionnaire session. The researcher distributed the questionnaire to all students. In the questionnaire there were five questions which were about the students’ responses of implementing the sticking pictures. The first question was about the material. There were twenty-four of the thirty two students choosing “A” as very interesting, eight of the thirty two students choosing “B” as interesting and no one chose option “C” as less interesting. The second question was about studying vocabulary by using the media. There were twenty-six of the thirty two students choosing option “A” as very interesting, five students for “B” as interesting and one student for “C” as less interesting. The third question was the response of the students about studying vocabulary through the sticking pictures. There were seventeen of the thirty two students choosing option “A” as very interested, fifteen of the thirty two students choosing “B” as interested and no one chose “C” as less interested. The fourth question was the response of the students about the easiest studying vocabulary by using the media. There were twenty of the thirty two students choosing “A” as very interesting to make them very easy to learn vocabulary through sticking pictures, twelve of the thirty two students choosing “B” as interesting and no one chose “C” as less interesting. For the last question was the respond of the students about the intention to study vocabulary through sticking pictures someday. There were thirty of the thirty two students choosing option “A” as very interested, two of the thirty two students choosing “C” as less interested and no one chose “B” as interested. It means that this media is recommended for the second graders. Because the responses of the students showed that they were very interested in studying vocabulary through sticking pictures So they wanted to study vocabulary by sticking pictures again. Conclusion Based on the result and discussion, it can be concluded that sticking pictures helped the students remember new vocabulary easily. There were two meetings of implementing sticking pictures in teaching vocabulary on animals to the second graders. The first and second meeting had similar activities during the teaching learning process. But in the second meeting, the media was applied in a game that still related to the media. The responses showed that the students were very excited to study vocabulary by using this media. Twenty-one students agreed that the media was very interesting. Seventeen students were very interested and enjoyed to study vocabulary through sticking pictures. Twenty students agreed that the implementation of sticking pictures helped them easily to remember the new vocabulary. There were thirty students who wanted to learn vocabulary by using this media again. It could be concluded that the implementation of sticking pictures was success in teaching vocabulary on animals to the second graders. References Chengqian, W. (2009) Methods For Teaching Primary Students EFL Vocabulary. Platteville: University of Wisconsin-Platteville. Harmer, J. (2012). Teacher Knowledge. Edinburg, England: Pearson Education Limited. Joklova, K. (2009). Using pictures in teaching vocabulary. 1-53. Fraenkel, J.R., & Wallen, N.E. (1996). How to Design and Evaluate Research in Education (3rd ed.). New York: McGraw-Hill State Council of Educational Research and Training Varun Marg, Defence Colony. (2011). Smart Performers Teachers Handbook For Primary Teachers. New Delhi: State Council of Educational Research and Training Varun Marg.